The Role of Islamic Boarding Schools in Improving the Quality of Islamic Primary School Education - Hasan, Moh. Ferdi (LP2M UIN Kiai Haji Achmad Siddiq Jember, 2024)
Basic education's pivotal role in enhancing human resource quality necessitates attention to improving Islamic Primary Schools (MI) in Indonesia. Despite being part of the basic education system, MIs face challenges in quality enhancement. Islamic boarding schools, as traditional educational institutions, have the potential to support MI development, yet this potential remains underexplored. This qualitative study employs a case study approach, utilizing interviews, observations, and document analysis for data collection. Islamic boarding schools significantly contribute to improving MI education quality through various means, including curriculum development, teacher provision, training, infrastructure support, and extracurricular collaboration. These contributions enhance both the processes and outcomes of MI education. The strategic partnership between Islamic boarding schools and MI is vital for advancing basic education quality in Indonesia. Strengthened collaboration is essential, leveraging the expertise of Islamic boarding schools in Islamic education and character building while providing MI with additional resources and support. Policy facilitation is necessary to encourage and enhance such partnerships, enriching the overall quality of basic education and integrating the unique values of Islamic boarding schools into the formal education system.